2022
DOI: 10.1002/jib.681
|View full text |Cite
|
Sign up to set email alerts
|

Production of non‐alcoholic beer via cold contact fermentation with Torulaspora delbrueckii

Abstract: Use of non-conventional yeasts are increasingly seen as a option for the production of low and alcohol-free beers. In this study, the application of four non-conventional yeasts -Kazachstania servazzii, Kluyevoromyces marxianus, Pichia fermentans and Torulaspora delbrueckii, originally isolated from sourdough cultures, for cold contact fermentations was assessed by screening their ability to reduce wort aldehydes at a fermentation temperature of 1.0 ± 0.5°C. Of the evaluated yeasts, Torulaspora delbrueckii was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…It cannot be conclusively explained as to why the wort flavor was noticeable as wort-derived aldehyde off-flavors are often degraded by the yeasts during fermentation. This has already been studied for selected non- Saccharomyces yeast strains in the context of cold contact fermentations for the production of non-alcoholic beers ( Nikulin et al, 2022 ). Consequently, it could be assumed that the yeast strain S. fib SF4 was also capable of degrading wort-derived aldehyde off-flavors, as the two beers fermented at 20°C did not exhibit this flavor attribute.…”
Section: Discussionmentioning
confidence: 99%
“…It cannot be conclusively explained as to why the wort flavor was noticeable as wort-derived aldehyde off-flavors are often degraded by the yeasts during fermentation. This has already been studied for selected non- Saccharomyces yeast strains in the context of cold contact fermentations for the production of non-alcoholic beers ( Nikulin et al, 2022 ). Consequently, it could be assumed that the yeast strain S. fib SF4 was also capable of degrading wort-derived aldehyde off-flavors, as the two beers fermented at 20°C did not exhibit this flavor attribute.…”
Section: Discussionmentioning
confidence: 99%
“…The base attribute list for the beer samples was formulated by four panel members in a consensus tasting session. Previous sensory profiles of VTT’s beers were used as templates [ 24 , 25 ]. This lexicon was introduced to the whole panel in panel training (divided in two groups).…”
Section: Methodsmentioning
confidence: 99%
“…It has also been shown that apart from Saccharomycodes ludwigii, there are also other strains that do not have the ability to ferment maltose and can be successfully used in the production of non-alcoholic beers. The authors examined and confirmed the usefulness of such strains as Cyberlindnera Saternus, Torulaspora delbrueckii or, for example, Mrakia gelida [25][26][27]. In addition, the biological method of producing non-alcoholic beers, which uses special strains of yeast, can have a number of benefits in beer production.…”
Section: Analysis Of Basic Physicochemical Parametersmentioning
confidence: 96%